“Efecto de fertilización en drench en la productividad de rebrote en variedades de ají pimentón (capsicum annuum L.) en la zona de Lamas” - Hoyos Cabrera, Jorge Luis (2006)
The p~esent investigation report had as objectives to determine the good dose and the eftect of NPK by means of the fertilization method Drench under conditions of sprouting the cultivation of pepper paprika and to determine the economic analysis of the treatments in study. lt was taken place in the denominated horticultura! field "Fundo El Pacifico", sector Killoallpa, Lamas district and province, San Martin region, south Latitude 6° 20' 15 ", West Longitude 76º 30' 45 ", Altitude 814 meters above sea level, area of life: tropical dry Forest, high lands forest of Peru, with precipitation averages yearly it is of 1200 mm and half temperature of 24 ° C. factorial experiment of 5 x 2 with three repetitions and 10 treatments was applied, adapted to the design block complete chance, making a total of 30 experimental units. The plant height, days of flowering, number of fruits for plant, longitude, diameter and weight of fruits, yield expressed in Kg. I there is and analysis cost benefit were evaluated. The fertilization level in Drench with 140 - 100 - 110 Kg. I ha of Nitrogen, Phosphorus and Potassium threw the best averages with yield in Kg. I ha with 5211.00 Kg. I ha for the ltalian Sweet variety (T3) and with 4310.67 Kg. I ha for the variety ANASAC (T4). The same treatments gave us relationships of benefit cost with 2.10 and 1.71. The ltalian Sweet variety threw bigger averages with 8.53, 8.32cm, 3.64cm and 38.37g for the number, longitude, diameter and weight of fruits. All this demonstrates us that the application of fertilizers using the fertilization system in Orench is profitable for the producer. The sprouting capacity is in relation to a good agronomic handling as appropriate and opportune pruning, watering and fertilization in order to achieve the biggest sprouting number in each plant, in the present work a sprouting of 99% of the total of pruned plants was achieved.